2021
DOI: 10.3390/ijerph18168745
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life and Risk Factors among Chinese Women in Japan Following the COVID-19 Outbreak

Abstract: The COVID-19 pandemic has significantly affected individuals’ physical and mental health, including that of immigrant women. This study aimed to evaluate the health-related quality of life (HRQoL), identify the demographic factors and awareness of the COVID-19 pandemic contributing to physical and mental health, and examine the risk factors associated with poor physical and mental health of Chinese women in Japan following the COVID-19 pandemic outbreak. Using an electronic questionnaire survey, we collected d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
(60 reference statements)
0
8
0
1
Order By: Relevance
“…Indeed, young Koreans living in Japan have higher suicide mortality than their Japanese counterparts ( Gilmour et al, 2019 ). The pandemic likely disproportionately affected the mental health of immigrants: increased anxiety due to COVID-19 has been noted among Chinese women living in Japan ( Luo & Sato, 2021 ), international students in China ( Fakhar et al, 2020 ), and immigrants in South Korea ( Acharya et al, 2021 ). Furthermore, research in Japan has found that infant mortality and stillbirth rates are significantly higher for immigrant women than their Japanese counterparts, in part due to language barriers, relatively low socioeconomic status, and underutilization of health care services ( Kita et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, young Koreans living in Japan have higher suicide mortality than their Japanese counterparts ( Gilmour et al, 2019 ). The pandemic likely disproportionately affected the mental health of immigrants: increased anxiety due to COVID-19 has been noted among Chinese women living in Japan ( Luo & Sato, 2021 ), international students in China ( Fakhar et al, 2020 ), and immigrants in South Korea ( Acharya et al, 2021 ). Furthermore, research in Japan has found that infant mortality and stillbirth rates are significantly higher for immigrant women than their Japanese counterparts, in part due to language barriers, relatively low socioeconomic status, and underutilization of health care services ( Kita et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…To practice ‘Zuoyuezi’, obtaining the support of an experienced person, such as a mother or mother-in-law, is necessary. However, the COVID-19 outbreak made it difficult to obtain family support [ 13 ]. Thus, providing postpartum care for Chinese women living in Japan is essential to help them get through the most challenging postpartum period, such as by extending the available period of postpartum care services.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Chinese women living in Japan with preschool-aged children reported high parenting-related stress and expressed a desire for childcare support [ 12 ]. Furthermore, a survey on the general population of immigrant Chinese women in Japan indicated that high coronavirus disease 2019 (COVID-19) concerns were related to poor mental health [ 13 ]. Therefore, improving this vulnerable population’s mental health—especially during the emergency pandemic period—is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…(E5) Analisando os relatos obtidos, verificou-se que todas as mulheres entrevistadas criaram estratégias para conseguirem atender aos múltiplos papéis desempenhados. As falas destacadas acima ainda reforçam o papel dessas mulheres de principais cuidadoras de suas famílias, responsabilidade que foi acentuada durante a pandemia, o que resultou no aumento da sobrecarga (Luo & Sato, 2021). Vale acrescentar que as que possuíam companheiro ou a mãe dividindo o contexto de responsabilidades naquele momento ainda relataram preocupações adicionais, como, por exemplo, a necessidade de momentos íntimos com o cônjuge ou o bem-estar da progenitora.…”
Section: Trabalho Remunerado Versus Trabalho Domésticounclassified